2023
DOI: 10.1039/d3nr02246c
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Au single atoms and Au nanoparticles on NiAl-LDH for selective electrooxidation of benzyl alcohol to benzaldehyde

Abstract: Introducing different active sites into heterogeneous catalysts provides new prospects to address the challenges in single-atom catalysis. Herein, the Au single atoms together and the Au nanoparticles were loaded onto...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Furthermore, the selectivity of AOR can also be adjusted through heteroatom doping. Song et al 134 reported an electrocatalyst, Au 1+ n -NiAl-LDH, which consists of both Au single atoms and Au nanoparticles on NiAl-LDH, achieving a high selectivity for the electrooxidation of benzyl alcohol to benzaldehyde (BAD). While pure NiAl-LDH displayed approximately 56% selectivity in the production of BAD, Au 1+ n -NiAl-LDH exhibited a significantly higher selectivity of 91%.…”
Section: Alcohol Electrooxidation Reactionmentioning
confidence: 99%
“…Furthermore, the selectivity of AOR can also be adjusted through heteroatom doping. Song et al 134 reported an electrocatalyst, Au 1+ n -NiAl-LDH, which consists of both Au single atoms and Au nanoparticles on NiAl-LDH, achieving a high selectivity for the electrooxidation of benzyl alcohol to benzaldehyde (BAD). While pure NiAl-LDH displayed approximately 56% selectivity in the production of BAD, Au 1+ n -NiAl-LDH exhibited a significantly higher selectivity of 91%.…”
Section: Alcohol Electrooxidation Reactionmentioning
confidence: 99%
“…Metal clusters have been proved to exhibit excellent electrocatalytic properties in various electrochemical reactions. 29–33 In this section, we introduce recent progress on the applications of metal clusters as electrocatalysts for the hydrogen evolution reaction (HER). The HER is a half-reaction of electrocatalytic water splitting that occurs at the cathode and which generally follows two possible mechanisms: the Volmer–Tafel mechanism and Volmer–Heyrovsky mechanism.…”
Section: Electrocatalytic H2 Productionmentioning
confidence: 99%